The Effect of Videoscribe Media Assisted by the Guided Inquiry Learning Model on Students’ Physics Learning Outcomes - Bervilza, Vashya Cheryl; Evendi, Evendi; Farhan, Ahmad; Wahyuni, Agus; Zainuddin, Zainuddin (Universitas Islam Negeri Ar-Raniry, 2026)
This research is motivated by the low learning outcomes in physics among students, which are influenced by the teacher-centered learning model and the limited use of innovative learning media. The aim of this study is to determine the effect of the guided inquiry model assisted by Videoscribe media on students’ physics learning outcomes. This research employed a quantitative approach with a quasi-experimental design involving two classes: an experimental class (XI Science 1) that used Videoscribe media within the guided inquiry model, and a control class (XI Science 2) that used the guided inquiry model without media assistance. The experimental and control classes consisted of 23 and 26 students, respectively. The instrument used in this study was a learning outcome test in the form of a pre-test and post-test. The average pre-test score in the experimental class was 39.13, which increased to 78.26 after treatment. In the control class, the average pre-test score was 34.61, increasing to 66.53 after treatment. Data analysis involved normality testing, homogeneity testing, and hypothesis testing, which showed a significant improvement in the learning outcomes of students in the experimental class compared to the control class. The results indicate that the guided inquiry learning model assisted by Videoscribe media has a positive effect on students’ physics learning outcomes on the topic of heat.